Value-Based Pricing Strategies in Retail: Effective or Not? - Petrovska, Ilijana; Šerovska, Gjorgjina; Kovačevski, Dimitar (Mednarodno inovativno poslovanje = Journal of Innovative Business and Management, 2019)
Customers are the key stakeholders for developing and running a successful business. From this perspective businesses must create positive perception in the eyes of their target customers. It is of key importance to create value proposition and the path for value creation can be very difficult. At the extreme, customers want great products with great quality for the lowest possible price. On a competitive market, it is the customer’s value perception that will determine the sales volumes of the products and services and the ultimate success of businesses. For this reason, companies have to choose pricing strategies based on the customers perceptions of the value products will bring to them. This paper focuses on the question whether using more customer oriented pricing strategies, such as value-based pricing strategy, in light of its benefits and disadvantages, is effective or not, especially considering the fact that most companies still use cost based and competitive based pricing strategies. Will it be effective if companies base their pricing strategies on the perceived value by the customers or it will be ineffective?